(untitled) (Journal of history, 2023)
Annotation. The author suggests analyzing the problems of national-territorial demarcation in Central Asia in the context of the general process of forming the federal image of the USSR. Researchers in the former Soviet republics and abroad have now made a number of clarifications and additions to the study of a complex range of issues on this problem, but discussions about the expediency, methods and results of nation-building in its Soviet version for the peoples of modern Central Asia remain relevant. Historians’ assessments often remain polar – from accusing the Bolshevik government of causing irreparable damage to the peoples to recognizing the progressive role of the creation of republics, which, practically in the form that developed in the 1920s and 1930s, became independent states after 1991. The study of facts and documents makes it possible to highlight the important role of local ethnoelites in the creation of the former Soviet republics of Central Asia and the Kazakh ASSR, the specifics of intraregional socio-economic and cultural ties, difficulties and contradictions in the transition from tradition to modernity. The cultural complexity of society, the multiple nature of the identity of representatives of different peoples, political and ethno-social components in their dynamics and interaction predetermined the ambiguous results of the demarcation and the historical inertia of their influence on the development and relations of modern states in the region. Keywords. USSR, ethno-national policy, nation-building, Central Asia, national-territorial division.